Computer interfaced remote control for solid state light switching / Hamzah Ismail - Ismail, Hamzah (1994)
This project describes a control circuit which is used to control the intensity of the light remotely (similar to light dimmer concept). The intensity of the light can be controlled by using a personal computer. Experimental results and a study of solid state light switching are also presented. The scope of project covers developing the transmitter and receiver unit, light sensor unit and control software.